An ecogeographical study of Vicia subgenus Vicia - Maxted, N. (1995)
An ecogeographic study of Vicia subgenus Vicia is presented. This group contains the cultivated vetches and their wild relatives. The subgenus contains 9 sections, 9 series, 38 species and 36 subspecific taxa. Ecogeographic data were recorded for each taxon throughout the geographical range of the subgenus. Future collection and conservation piorities are discussed and specific targets for ex situ and in situ are identified.